Causation between occupational disease and death: a forensic medical evaluation - Liman, Zafer; Kayhan, Uğur; Erelel, Mustafa; Üzün, İbrahim (The Bulletin of Legal Medicine, 2025)
Objective: This study examines the challenges encountered in the forensic evaluation of causal links in occupational disease-related deaths in Türkiye. Methods: A total of 202 case files reviewed retrospectively by the First Specialization Board of the Council of Forensic Medicine between 2008 and 2012 were included. These cases were assessed to determine whether death was attributable to an occupational disease. Case characteristics, duration of employment, intervals between diagnosis and death, presence of histopathological evaluation, and expert opinions were analyzed. Results: All cases involved male individuals, and 91.1% had worked in the coal mining sector. The mean duration of employment was 23.5 years, while the average time between diagnosis and death was 19.4 years. Pneumoconiosis was reported in the medical history of 92.6% of cases. Based on expert evaluations, 89.6% were diagnosed with an occupational disease, and in 15.8%, the death was attributed to the disease. Autopsy was performed in only one case (0.5%). No statistically significant relationship was found between duration of employment, time from diagnosis to death, or post-retirement lifespan and expert opinion on causality (p>0.05). However, comorbid systemic diseases were significantly associated with negative causality assessment (p<0.05). Conclusion: Most cases lacked autopsy data, had long intervals between diagnosis and death, and showed incomplete medical documentation. The lack of documentation, absence of autopsy, and presence of comorbidities were the main factors complicating the determination of whether death was due to occupational disease. To improve recognition and documentation, structured forensic autopsy protocols and a national registry system are urgently needed.